Al2O3 films grown by glow discharge plasma aluminising. (July 2014) - Jamnapara, N. I.; Nayak, V.; Avtani, D. U.; Chauhan, N. L.; Panda, D.; Gupta, S. B.; Kalaria, K.; Vaghela, N.; Mukherjee, S.; Khanna, A. S.
Abstract : Aluminising of 9Cr steel substrates followed by heat treatment has been attempted to generate Al2 O3 films along with Fe–Al diffusion zone at the coating/substrate interface. Effect of glow discharge plasma processing on the phase and microstructure of resultant alumina films in comparison with thermally processed samples has been reported. The thermal and plasma treated samples were characterised using X-ray diffraction, scanning electron microscopy–energy dispersive X-ray spectroscopy, electron probe microanalysis, X-ray photoelectron spectroscopy (XPS) and nanoindentation techniques. X-ray diffraction and XPS studies revealed γ-Al2 O3 phase in both thermal and plasma processed samples. The XPS data indicated higher binding energies in plasma processed Al2 O3 films as compared to thermally processed Al2 O3 films. Scanning electron microscopy observations revealed cracks in thermally grown Al2 O3 films while the same was not observed in plasma processed films. The EDX analysis revealed Fe(Al) diffusion layer of ∼3 μm in plasma processed films while the same was not observed in thermally treated samples. Nanoindentation tests on plasma grown alumina films indicated 16·96 GPa hardness while hardness for thermally grown alumina films was found to be 9·95 GPa. The role of plasma in generating a crack free alumina film has been discussed.